Reproduktionsleistung hochleistender Milchkühe: Auswirkungen für die Praxis - de Kruif, A.; Leroy, J.; Opsomer, G. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2008)
Several studies have clearly demonstrated that the fertility of high yielding dairy cows has declined over the past 25 years. The resumption of ovarian activity post partum has been retarded and conception rates have dropped significantly from 55 to 40%. Accordingly, the calving interval has increased from about 385 days to 417 days. The percentage of cows culled because of infertility has risen from 5 to 8% per year. The “subfertility syndrome” is a multifactorial problem. As the negative energy balance and general health status after calving are known to be paramount factors hampering fertility, it is apparent that avoiding both is among the most important preventive measures to be taken. Improvement of the energy status by achieving a high dry matter intake and the provision of optimal and well balanced nutrition during the transition period as well as during early lactation are key goals in this effort. To achieve these goals, we should not only calculate the rations on paper, but should also check in the stable to determine whether the calculated amount is really being consumed by the cows. Furthermore, veterinarians should use their “clinical eyes” as well as other diagnostic tools to assess the general health status of the cows and to assess at which aspect of the process things are going wrong and need to be adjusted. Besides the control of the negative energy balance and health status, other management factors that need to be maximized include heat detection, cow comfort, insemination technique, time of insemination during estrus and sperm quality. Only if management is on a very high level high milk production and good fertility can be a feasible combination.
Keywords: Milchkuh; Milchproduktion; Reproduktionsstörungen; Management